Penerapan E-Commerce Dalam Meningkatkan Daya Saing Usaha - Harsya Haryo Prastya; Muhammad Irwan Padli Nasution (Journal Of Informatics And Busisnes, 2024)
In the digital age, the use of e-commerce has become an important strategy for increasing business competitiveness. The focus of this research is how can use e-commerce to increase market share, improve operational efficiency, and provide customers with a better experience. The research uses literature research and data analysis from various that have been successful in using ecommerce. Research results show that can not only expand market reach geographically but can also optimize supply chains, reduce operating costs, and provide more customer-friendly service. In short, using e-commerce has become one of the most important ways for to become more competitive amid increasing global competition.